Family Ecology Modeling In Care For Family Members With Chronic Tuberculosis In Mekon Indah, Kupang District - Weraman, Pius; Basri, Muntasir; Keraf, Anastasia Sofia L. (Journal of Neonatal Surgery, 2025)
The results of Elisa Hapasari's research on ecotherapy for cancer patients, Interpretative Phenomenological Analysis on members of the Confucian Union Community of Charity show that this ecotherapy contributes sufficiently to cancer healing. Based on this experience, various unresolved problems were found, such as ecotherapy to support the healing of common diseases using the same approach model. The therapy model is generated by adding the fulfillment of needs, biological, psychological, sociological and spiritual at one meeting to deal with family problems. The purpose of this study was to apply the ecotherapy model experienced by participants through Healthy Life Guidance (BHS) or Love Configuration Union (SKK) in biological, psychological, sociological and spiritual therapy for families, implementation and evaluation of the implementation of family ecotherapy and conducting trials of a therapy model based on the results of the development of family ecotherapy on the quality level of the family in caring for family members, the model trial was carried out in the Mekon Indah area of Kupang City with a total sample of 71 respondents. This study used a quasy experimental design with non-equivalent group pretest and posttest design methods, because it was considered to have better internal and external validity. Researchers used two non-equivalent groups, one group functioning as a control group, and another group functioning as a treatment group. The instrument used was the DASS 42 questionnaire. The statistical test used was the Wilcoxon Signed Rank Test to see differences in patients before and after taking ecotherapy treatment through Healthy Life Guidance (BHS) in this Love Configuration Union. The results showed depression, anxiety and stress in patients with a P value <0.05 so it can be concluded that there are differences in the psychological burden of patients getting better after participating in ecotherapy treatment at Mekon Indah. Almost all of the patients interviewed also showed biological signs that the disease they were suffering from also began to decrease and heal. 05 so that it can be concluded that there are differences in the condition of the patient's psychological burden getting better after participating in ecotherapy treatment at Mekon Indah. Almost all of the patients interviewed also showed biological signs that the disease they were suffering from also began to decrease and heal. 05 so that it can be concluded that there are differences in the condition of the patient's psychological burden getting better after participating in ecotherapy treatment at Mekon Indah. Almost all of the patients interviewed also showed biological signs that the disease they were suffering from also began to decrease and heal.